SACRAL INSUFFICIENCY FRACTURES: A CASE REPORT AND REVIEW OF THE LITERATURE - Birol Balaban,; Evren Yaşar,; Arif Kenan Tan,; Tunç Alp Kalyon,; Murat Kocaoğlu, (Archives of Rheumatology, 2005)
Sacral insufficiency fracture, a type of stress fracture of postmenopausal older women, results from normal physiologic stress placed on abnormal bone with deficient elastic resistance. Low back, pelvic and groin pain that limit mobilization of the patients are seen in sacral insufficiency fractures. Bone scintigraphy and computerized tomography are common tools in diagnosis. Increased H-shaped uptake pattern in bone scintigraphy is a pathognomonic sign of bilateral fracture of sacral ala. In this case report, a 82 years old woman with sacral insufficiency fracture is presented. This pathology should be considered in the differential diagnosis of low back or pelvic pain in older patients with osteoporosis.